Bad hombres [videorecording (DVD)] - Jane, Thomas; Hemsworth, Luke, 1980-; Cassavetes, Nick; Tyrese (Screen Media, 2024)
"Welcome to the land of opportunity₄ Two undocumented immigrants take on a simple job. They have to dig a hole somewhere in no man's land. When they discover that their two clients turn out to be psychopathic criminals, the immigrants must survive the upcoming night. A much more difficult job than expected.